Upfront Surgical Resection of Melanoma Brain Metastases Provides a Bridge Toward Immunotherapy‐Mediated Systemic Control. (22nd February 2019) - Alvarez‐Breckenridge, Christopher; Giobbie‐Hurder, Anita; Gill, Corey M.; Bertalan, Mia; Stocking, Jackson; Kaplan, Alexander; Nayyar, Naema; Lawrence, Donald P.; Flaherty, Keith T.; Shih, Helen A.; Oh, Kevin; Batchelor, Tracy T.; et al.
Abstract: Background: Immune checkpoint blockade has systemic efficacy in patients with metastatic melanoma, including those with brain metastases (MBMs). However, immunotherapy‐induced intracranial tumoral inflammation can lead to neurologic compromise, requiring steroids, which abrogate the systemic efficacy of this approach. We investigated whether upfront neurosurgical resection of MBM is associated with a therapeutic advantage when performed prior to initiation of immunotherapy. Material and Methods: An institutional review board‐approved, retrospective study identified 142 patients with MBM treated with immune checkpoint blockade between 2010 and 2016 at Massachusetts General Hospital, of whom 79 received surgery. Patients were classified based on the temporal relationship between immunotherapy, surgery, and development of central nervous system metastases. Overall survival (OS) was calculated from the date of diagnosis of MBM until death from any cause. Multivariate model building included a prognostic Cox model of OS, the effect of immunotherapy and surgical sequencing on OS, and the effect of immunotherapy and radiation sequencing on OS. Results: The 2‐year overall survival for patients treated with cytotoxic T‐lymphocyte antigen 4, programmed death 1, or combinatorial blockade was 19%, 54%, and 57%, respectively. Among immunotherapy‐naïve melanoma brain metastases, surgery followed by immunotherapy had a median survival of 22.7 months (95% confidence interval [CI], 12.6–39.2) compared with 10.8 months for patients treated with immunotherapy alone (95% CI, 7.8–16.3) and 9.4 months for patients treated with immunotherapy followed by surgery (95% CI, 4.1 to ∞; p  = .12). On multivariate analysis, immunotherapy‐naïve brain metastases treated with immunotherapy alone were associated with increased risk of death (hazard ratio, 1.72; 95% CI, 1.00–2.99) compared with immunotherapy‐naïve brain metastases treated with surgery followed by immunotherapy. Conclusion: In treatment‐naïve patients, early surgical resection for local control should be considered prior to commencing immunotherapy. A prospective, randomized trial comparing the sequence of surgery and immunotherapy for treatment‐naïve melanoma brain metastases is warranted. Abstract : Nearly 75% of patients with stage IV melanoma will develop brain metastases as a sequelae of their illness and approximately 50% will succumb to progression of their intracranial disease. Standard therapy includes surgery, but the therapeutic landscape for metastatic melanoma is being transformed by immunotherapy blockade treatment possibilities. Considering the limited data informing the combination of surgery and immunotherapy for metastatic melanoma, the study reported here investigated the timing of neurosurgical intervention and immune checkpoint blockade.